Integration of Fiqh and Science in Determining Fajr Time in Indonesia - Sakirman Sakirman; A Jamil; Moelki Fahmi Ardliansyah (KEDJATI Journal of Islamic Civilization, 2024)
Fiqh and science are two entities that must be brought together to determine the time of dawn (fajr). Fajr has three signs: fajr prayer time, forbidden food for fasting people, and the final limit of wukuf time in Arafat for pilgrims. Meanwhile, inaccuracy in the determination of dawn can result in the invalidity of some acts of worship. This study aims to observe the determination of Fajr time in Indonesia. This field research used a qualitative approach with primary data from observation of dawn in the field using a pocket photometer tool in the form of a Sky Quality Meter. The observation results were then processed using scientific approaches, such as ImageJ, Gnuplot, and Microsoft Excel, to get a graph/curve that can translate the sun's height in determining dawn time. The research findings showed that the rise of dawn is related to the criteria for the beginning of Fajr time. The sun's altitude is related to the position of how many degrees the beginning of fajr shadiq began to be seen; from the data that was successfully processed, the emergence of fajr shadiq right at the sun's altitude was -20 °. In fiqh terms, (1) the difference at the beginning of dawn has an impact on the problem of prayer; the invalidity of people who hasten to pray at dawn once they hear the call to dawn, such as because of illness, staying up all night, travelling, and praying at home for women. Because it has not yet entered the time of prayer (dukhul al-waqt); (2) menstrual and postpartum blood for women who stop during the limit period if based on the existing dawn schedule, the woman is not obliged to fast because it stops shortly after the start of the adhan, while if according to another schedule, the time of cessation of blood is still counted before imsak, so it should be pure and the obligation to fast; and (3) about the Sunnah of delaying the suhoor meal, and the dawn prayer becomes inappropriate.